Modulation of the mtrCDE‐encoded efflux pump gene complex of Neisseria meningitidis due to a Correia element insertion sequence - Rouquette‐Loughlin, Corinne E.; Balthazar, Jacqueline T.; Hill, Stuart A.; Shafer, William M. (Molecular microbiology, 2004)
Summary The mtr (multiple transferable resistance) gene complex in Neisseria gonorrhoeae encodes an energy‐dependent efflux pump system that is responsible for export of anti‐bacterial hydrophobic agents. Expression of the mtrCDE operon in gonococci is negatively regulated by the MtrR protein. Hydrophobic agent resistance mediated by the mtr system is also inducible, which results from an AraC‐like protein termed MtrA. In this work, we identified and characterized a pump similar to the gonococcal mtr system in various strains of Neisseria meningitidis. Unlike the situation with gonococci, the mtr system in meningococci is not subject to the MtrR or MtrA regulatory schemes. An analysis of the promoter region of the mtrCDE operon in a panel of meningococcal strains revealed the presence of one or two classes of insertion sequence elements. A 155–159 bp insertion sequence element known as the Correia element, previously identified elsewhere in the gonococcal and meningococcal genomes, was present in the mtrCDE promoter region of all meningococcal strains tested. In addition to the Correia element, a minority of strains had a tandemly linked, intact copy of IS1301. As described previously, a binding site for the integration host factor (IHF) was present at the centre of the Correia element upstream of mtrCDE genes. IHF was found to bind specifically to this site and deletion of the IHF binding site enhanced mtrC transcription. We also identified a post‐transcriptional regulation of the mtrCDE transcript by cleavage in the inverted repeat of the Correia element, as previously described by Mazzone et al. [Gene278: 211–222 (2001)] and De Gregorio et al. [Biochim Biophys Acta 1576: 39–44 (2002)]for other Correia element. We conclude that the mtr efflux system in meningococci is subject to transcriptional regulation by IHF and post‐transcriptional regulation by cleavage in the inverted repeat of the Correia element.